2012
DOI: 10.1021/ic300661c
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Selective Fluorescent Sensor for Distinguishing Cadmium from Zinc Ions Based on a Quinoline Platform

Abstract: A fluorescent sensor, N-(quinolin-8-yl)-2-(quinolin-8-yloxy)acetamide (HL), based on 8-aminoquinoline and 8-hydroxyquinoline platforms has been synthesized. This sensor displays high selectivity and sensitive fluorescence enhancement to Cd(2+) in ethanol. Moreover, sensor HL can distinguish Cd(2+) from Zn(2+) via two different sensing mechanisms (photoinduced electron transfer for Cd(2+); internal charge transfer for Zn(2+)). The composition of the complex Cd(2+)/HL or Zn(2+)/L(-) has been found to be 1:1, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(76 citation statements)
references
References 53 publications
0
75
0
Order By: Relevance
“…(1) (2) The least-square analysis of experimental data gave the following set of parameters: J = -0.87 cm -1 , zJЈ = -0.41, g = 2.23 with the agreement factor R 2 = 0.99985. The small negative value of J suggests a weak antiferromagnetic interaction between Mn II ions within the dimers, which is mediated by the double syn-syn mode μ 2 -carboxyl bridges.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) (2) The least-square analysis of experimental data gave the following set of parameters: J = -0.87 cm -1 , zJЈ = -0.41, g = 2.23 with the agreement factor R 2 = 0.99985. The small negative value of J suggests a weak antiferromagnetic interaction between Mn II ions within the dimers, which is mediated by the double syn-syn mode μ 2 -carboxyl bridges.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…[1][2][3][4][5][6] In order to discover novel functional materials in the field of CPs, the rational design and assembly of metal ions and various multifunctional ligands is sensible and effective. [7][8][9][10][11][12] The numerous literatures indicated that utilizing mixed ligands, usually including a multidentate carboxylate ligand and a flexible bipyridyl ligand, to obtain target compound is the most common strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the carboxamidoquinoline derivatives have attracted much attention for their tunable bonding mode. According to the types of the auxiliary binding sites and the center metal ions (Scheme 1), the carboxamidoquinoline ligands can bind with metal ions in an amide tautomeric form (type I) [30][31][32], an imidic acid tautomeric form (type II) [33,34], and a deprotonation amide tautomeric form (type III) [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…With tunable and suitable coordination structure, some sophisticated carboxamidoquinoline-base sensors for recognition of various metal ions, such as Zn 2+ , Cd 2+ and Cu 2+ , have been developed [30][31][32][33][34][35][36][37][38][39][40]. However, systems for recognition of Hg 2+ are still unknown, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%